2011
DOI: 10.1090/s0002-9939-2011-10730-5
|View full text |Cite
|
Sign up to set email alerts
|

Martin’s maximum and weak square

Abstract: Abstract. We analyse the influence of the forcing axiom Martin's Maximum on the existence of square sequences, with a focus on the weak square principle λ,μ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Magidor also showed that Martin's Maximum (MM) implies the failure of κ,κ for every uncountable κ with cf(κ) = ω. Then Cummings and Magidor [1] obtained sharp results on the greatest extent of κ,κ that is compatible with MM. Magidor also considered the influence of the axiom DPFA, the analogue of PFA for proper posets that do not add any reals.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Magidor also showed that Martin's Maximum (MM) implies the failure of κ,κ for every uncountable κ with cf(κ) = ω. Then Cummings and Magidor [1] obtained sharp results on the greatest extent of κ,κ that is compatible with MM. Magidor also considered the influence of the axiom DPFA, the analogue of PFA for proper posets that do not add any reals.…”
Section: Introductionmentioning
confidence: 65%
“…∈ Y , and hence that for any α ∈ Y , α < γ and σ α (1) is defined. Define a coloring c : (1)] because an infinite strictly decreasing sequence of ordinals can be built from this. So there are two cases to consider.…”
Section: Notationmentioning
confidence: 99%
“…Proof. The definitions of * λ and λ,ℵ1 may be found in [CM11], and the model we construct is a slight variation of the model V 3 from Section 3 of that paper. Specifically, we start by working in the model V 1 from [CM11, §3] so that κ is a supercompact cardinal indestructible under (< κ)-directed-closed notions of forcing, and CH λ holds for all cardinals λ ≥ κ.…”
Section: Sample Corollariesmentioning
confidence: 99%
“…We end this section by briefly remarking on two other models in which bad scales exist. A result of Magidor [5] shows that, if Martin's Maximum holds, then any scale of length ℵ ω+1 in A ℵ n , where A ⊆ ω, is bad. Foreman and Magidor, in [6], show that the same conclusion follows from the Chang's Conjecture (ℵ ω+1 , ℵ ω ) ։ (ℵ 1 , ℵ 0 ).…”
Section: Classifying Bad Pointsmentioning
confidence: 99%